Ranking of Job Applicants, On-the-job Search, and Persistent Unemployment - Stefan Eriksson; Nils Gottfries (Uppsala University, Department of Economics, 2003)
We formulate an efficiency wage model with on-the-job search where wages depend on turnover and employers may use information on whether the searching worker is employed or unemployed as a hiring criterion. We show theoretically that ranking by employment status affects both the level and the persistence of unemployment and numerically that these effects are substantial. More prevalent ranking in Europe compared to the US - because of more rigid wage structures etc. - could potentially help to explain the high and persistent European unemployment.
urn:nbn:se:uu:diva-2477
Keywords: E24; J64; 330; Efficiency wage; Turnover; On-thejob search; Persistence; Ranking; Unemployment; Unions; Arbeitsmarkttheorie; Effizienzlohn; Arbeitsuche; Arbeitsmobilität; Vergleich; USA; EU-Staaten